Response of Tomato Fruit Quality Depends on Period of LED Supplementary Light - Wang, Shuya; Jin, Ning; Jin, Li; Xiao, Xuemei; Hu, Linli; Liu, Zeci; Wu, Yue; Xie, Yandong; Zhu, Wen; Lyu, Jian; Yu, Jihua (Frontiers in Nutrition, 2022)
Light is an important environmental factor that regulates the activity of metabolism-related biochemical pathways during tomato maturation. Using LED to improve lighting conditions during the process of tomato growth and development is a feasible and efficient method to improve the quality of tomato fruit. In this study, red and blue LEDs were used to supplement light on “MicroTom” tomato plants for different periods of time in the morning and evening, and the differences between the primary and secondary metabolites and other nutrient metabolites in the tomato fruit were analyzed using liquid chromatography and liquid chromatography mass spectrometry and other methods. Supplementing light in the morning promoted the accumulation of vitamin C, organic acids, amino acids, carotenoids, phenolic acids, and other health-promoting substances in the tomato fruits. Supplementing light in the evening significantly increased the content of sugars, flavonoids, and aromatic substances in tomato fruits, whereas the promoting effect of LED on the accumulation of amino acids and carotenoids was lower in the evening than in the morning. Both morning and evening light supplementation reduced the mineral content of fruit. In conclusion, morning light supplementation improved the nutritional quality of tomato fruits, while evening light supplementation improved their flavor.